Działalność edukacyjna kobiet-Polek w Wielkim Księstwie Poznańskim w drugiej połowie XIX wieku jako czynnik kształtowania świadomości narodowej = The educational activity of Polish women in the Grand Duchy of Posen in the second half of the 19th century as the factor influencing the shape of the national identity - Wyder, Grażyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
At the turn of the 19th and 20th centuries, the Germanization of the Grand Duchy of Posen became stronger. The role of the Polish language in education was significantly repressed. Polish language was gradually eliminated from schools. Society`s impoverishment made the private education impossible.
Keywords: Wielkie Ksiestwo Poznańskie; edukacja; kobiety; Świadomość narodowa - Polska - 19-20 w.